Inverse polynomials

If g(x)g(x) is inverse of a polynomial f(x)f(x) then f(g(x))=xf(g(x))=x

Inverse of Linear polynomial function

Let there be a linear polynomial f(x)=ax+bf(x)=ax+b; it's inverse function g(x)=xbag(x)=\frac{x-b}{a}

Proof:

Let the inverse of f(x)f(x) be g(x)g(x) f(g(x))=x\Rightarrow f(g(x))=x ag(x)+b=x\Rightarrow ag(x)+b=x g(x)=xba\Rightarrow g(x)=\frac{x-b}{a}

Inverse of Quadratic polynomial function

Let there be a quadratic polynomial f(x)=ax2+bx+cf(x)=ax^2+bx+c; it's inverse function g(x)=b+b2+4a(xc)2ag(x)=\frac{-b{^{+}_{-}}\sqrt{b^2+4a(x-c)}}{2a}

Proof:

Let inverse of f(x)f(x) be g(x)g(x) f(g(x))=x\Rightarrow f(g(x))=x ag2(x)+bg(x)+c=x\Rightarrow ag^2(x)+bg(x)+c=x g2(x)+bag(x)+ca=xa\Rightarrow g^2(x)+\frac{b}{a}g(x)+\frac{c}{a}=\frac{x}{a} g2(x)+bag(x)=xca\Rightarrow g^2(x)+\frac{b}{a}g(x)=\frac{x-c}{a} (g(x)+b2a)2b24a2=xca\Rightarrow (g(x)+\frac{b}{2a})^2-\frac{b^2}{4a^2}=\frac{x-c}{a} (g(x)+b2a)2=xca+b24a2=4a(xc)+b24a2\Rightarrow (g(x)+\frac{b}{2a})^2=\frac{x-c}{a}+\frac{b^2}{4a^2}=\frac{4a(x-c)+b^2}{4a^2} g(x)+b2a=+b2+4a(xc)2a\Rightarrow g(x)+\frac{b}{2a}=\frac{{^{+}_{-}}\sqrt{b^2+4a(x-c)}}{2a} g(x)=b+b2+4a(xc)2a\Rightarrow g(x)=\frac{-b{^{+}_{-}}\sqrt{b^2+4a(x-c)}}{2a}

Inverse of any nn degree polynomial

Let there be a nn degree polynomial f(x)=k=0nakxkf(x)=\sum_{k=0}^{n}a_kx^k and let there be a function z(x0,x1...,xn)z(x_0,x_1...,x_n) which takes the the coefficients of any nn degree polynomial and gives it's zeroes as output (the first input is the constant term, next is the linear and so on), then the inverse function of f(x)f(x) is g(x)=z(a0x,a1,a2...,an)g(x)=z(a_0-x,a_1,a_2...,a_n)

Proof:

Let inverse of f(x)f(x) be g(x)g(x) f(g(x))=x\Rightarrow f(g(x))=x angn(x)+an1gn1(x)...a1g(x)+a0=x\Rightarrow a_ng^n(x)+a_{n-1}g^{n-1}(x)...a_1g(x)+a_0=x angn(x)+an1gn1(x)...a1g(x)+a0x=0\Rightarrow a_ng^n(x)+a_{n-1}g^{n-1}(x)...a_1g(x)+a_0-x=0 g(x)=z(a0x,a1,a2...,an)\Rightarrow g(x)=z(a_0-x,a_1,a_2...,a_n)


Example of last statement:

For degree 2: z(x0,x1,x2)=x1+x124x2x02x2z(x_0,x_1,x_2)=\frac{-x_1{^{+}_{-}}\sqrt{x_1^2-4x_2x_0}}{2x_2} \therefore For a function f(x)=ax2+bx+cf(x)=ax^2+bx+c with inverse function as g(x)g(x) g(x)=z(cx,b,a)=b+b24a(cx)2a=b+b2+4a(xc)2ag(x)=z(c-x,b,a)=\frac{-b{^{+}_{-}}\sqrt{b^2-4a(c-x)}}{2a}=\frac{-b{^{+}_{-}}\sqrt{b^2+4a(x-c)}}{2a}

#Algebra

Note by Zakir Husain
1 year ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Really good! @Zakir Husain.

I have another idea for a note of yours:

A proof of Euler's identity!

×

Problem Loading...

Note Loading...

Set Loading...